19. EFEKTIVITAS KERJA SAMA INDONESIA – FILIPINA DALAM PENANGANAN KASUS IUU FISHING OLEH FILIPINA DI PERAIRAN INDONESIA PERIODE 2008 – 2014 - Fiesca Novsella Ayuningtyas; Tri Cahyo Utomo; Shary Charlotte P (Journal of International Relations Diponegoro, 2016)
Indonesia is the largest archipelago in the world with around 17,506 of islands and a coastlineof 81,900 km. Indonesian territory which is 2/3 of it is the water area certainly has a lot ofnatural resources either biological or non biological, therein including fisheries. IUU Fishingin Indonesia has a fairly high frequency rate, especially by neighboring countries, Philippines.Indonesia and Philippines have made efforts of cooperation in order to combat IUU Fishing.The purpose of this study is to understand the impact that may result from IUU fishingactivities, especially for Indonesia and to analyze how effective the cooperation between theGovernment of Indonesia and the Government of Philippines in handling cases of IUUFishing. The type of causal comparative research is used in this study to explain the causalrelation that influences the effectiveness of cooperation between the Government of Indonesiaand the Government of Philippines in the handling of IUU fishing in Indonesian waters. Theresults of this study indicates that such cooperation is effective in combating IUU fishing inthe waters of Indonesia by the Filipinos, but has not achieve optimal results yet.Improvements by both government of Indonesia and Philippines is necessary, to realize thesecurity and stability of Indonesian waters comprehensively.